Comparative analysis of porcine-uterine decellularization for bioactive-molecule preservation and DNA removal - Fazel Anvari Yazdi, Abbas; Tahermanesh, Kobra; Ejlali, Maryam; Babaei-Ghazvini, Amin; Acharya, Bishnu; Badea, Ildiko; MacPhee, Daniel J.; Chen, Xiongbiao (Frontiers in Bioengineering and Biotechnology, 2024)
Decellularized uterine extracellular matrix has emerged as a pivotal focus in the realm of biomaterials, offering a promising source in uterine tissue regeneration, research on disease diagnosis and treatments, and ultimately uterine transplantation. In this study, we examined various protocols for decellularizing porcine uterine tissues, aimed to unravel the intricate dynamics of DNA removal, bioactive molecules preservation, and microstructural alterations. Porcine uterine tissues were treated with 6 different, yet rigorously selected and designed, protocols with sodium dodecyl sulfate (SDS), Triton ® X-100, peracetic acid + ethanol, and DNase I. After decellularization, we examined DNA quantification, histological staining (H&E and DAPI), glycosaminoglycans (GAG) assay, scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FT-IR), X-ray photoelectron spectroscopy (XPS), and Thermogravimetric Analysis (TGA). Then, a comparative analysis among all 6 protocols was conducted with the results demonstrating that all protocols achieved decellularization; while 0.1% SDS + 1% Triton ® X-100, coupled with agitation, demonstrated highest efficiency in DNA removal. Also, it was found that DNase I played a key role in enhancing the efficiency of the decellularization process with underscoring its significance in digesting cellular contents and eliminating cell debris by 99.79% (19.63 ± 3.92 ng/mg dry weight). Taken together, our findings enhance the nuanced understanding of DNA removal, GAG preservation, microstructural alteration, and protein decomposition in decellularized uterine extracellular matrix, while highlighting the importance of decellularization protocols designed for intended applications. This study along with our findings represents meaningful progress for advancing the field of uterine transplantation and related tissue engineering / regenerative medicine.